Lizards from the Lost World: two new species and evolutionary relationships of the Pantepui highland Riolama (Gymnophthalmidae). Issue 1 (27th January 2020) - Recoder, Renato; Prates, Ivan; Marques-Souza, Sergio; Camacho, Agustín; Nunes, Pedro M Sales; Dal Vechio, Francisco; Ghellere, José Mario; McDiarmid, Roy W; Rodrigues, Miguel Trefaut
Abstract: The Pantepui region of northern South America harbours an endemic fauna that differs dramatically from those of the surrounding lowland rainforests and savannas. A component of this unique fauna is Riolama, a poorly known genus of microteiid lizards with four described and two undescribed species restricted to tepui mountains. We here implement an integrative approach to formally describe the two unnamed species and investigate the phylogenetic relationships and timing of diversification in Riolama using a fossil-calibrated molecular approach. Our results suggest that diversification initiated in Riolama during the Oligocene ( c. 28 Mya), thereby characterizing the genus as an ancient lineage. This supports the Plateau biogeographic hypothesis to explain the diversification of the Pantepui fauna. Our divergence time estimation analysis also provides an updated temporal framework for the diversification of the highly diverse Gymnophthalmidae clade.